2017
DOI: 10.3945/ajcn.117.156349
|View full text |Cite
|
Sign up to set email alerts
|

Association of TCN2 rs1801198 c.776G>C polymorphism with markers of one-carbon metabolism and related diseases: a systematic review and meta-analysis of genetic association studies

Abstract: Background: Vitamin B-12 (cobalamin) deficiency may produce severe neurologic and hematologic manifestations. Approximately 20-25% of circulating cobalamin binds to transcobalamin 2 (TCN2), which is referred to as active vitamin B-12. The G allele of the TCN2 c.776G.C (rs1801198) polymorphism has been associated with a lower plasma concentration of holotranscobalamin. However, genotype association studies on rs1801198 have led to conflicting results regarding its influence on one-carbon metabolism (OCM) marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Transcobalamin 2 (TCN2) is a protein that is essential for binding circulating vitamin B12 for its transport into cells (Oussalah, Levy, Filhine-Tresarrieu, Namour, & Gueant, 2017). TCN2 polymorphism affects not only its expression but ultimately its plasma concentration and thus the availability of vitamin B12 to aid in re-methylation of Hcy (Oussalah et al, 2017). The C > G substitution alters the structure of the TCN2 protein affecting its affinity for vitamin B12, resulting in easier release from the bound TCN2 transporter (Afman, Lievers, van der Put, Trijbels, & Blom, 2002;Joslin, Green, German, & Lange, 2014) (Furness et al, 2013;Furness, Yasin, Dekker, Thompson, & Roberts, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcobalamin 2 (TCN2) is a protein that is essential for binding circulating vitamin B12 for its transport into cells (Oussalah, Levy, Filhine-Tresarrieu, Namour, & Gueant, 2017). TCN2 polymorphism affects not only its expression but ultimately its plasma concentration and thus the availability of vitamin B12 to aid in re-methylation of Hcy (Oussalah et al, 2017). The C > G substitution alters the structure of the TCN2 protein affecting its affinity for vitamin B12, resulting in easier release from the bound TCN2 transporter (Afman, Lievers, van der Put, Trijbels, & Blom, 2002;Joslin, Green, German, & Lange, 2014) (Furness et al, 2013;Furness, Yasin, Dekker, Thompson, & Roberts, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We also found an association between the maternal TCN2 C776G (GG) genotype and a decreased risk for sPTB. Transcobalamin 2 (TCN2) is a protein that is essential for binding circulating vitamin B12 for its transport into cells (Oussalah, Levy, Filhine‐Tresarrieu, Namour, & Gueant, 2017). TCN2 polymorphism affects not only its expression but ultimately its plasma concentration and thus the availability of vitamin B12 to aid in re‐methylation of Hcy (Oussalah et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Six SNPs were included in this study: MTHFR 677 (rs1801133), MTHFR 1298 (rs1801131), MTHFD1 1958 (rs2236225), MTR 2756 (rs1805087), MTRR 66 (rs1801394), TCN2 776 (rs1801198). Supplementary Table S1 describes the chromosomal location of each SNP, the enzyme encoded by the associated gene, enzyme function and effect of the polymorphism [ 6 , 22 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…TCN-2 has ~8291 polymorphisms, out of which 1183 are deletions, 02 are multiple base substitutions, 146 are repeat variations, and 6960 are SNPs 107 . One common polymorphism in the TCN 2 gene is a G to C substitution (776 G > C, rs1801198) that results in replacement of a proline with an arginine 108 In a recent meta-analysis, it was shown that subjects with the rs1801198 GG genotype had significantly lower concentrations of holotranscobalamin and higher Hcy levels compared to subjects with the rs1801198 CC genotype. This polymorphism has also been shown to be associated with different cancers, including colorectal cancer, ovarian cancer, glioblastoma, among others.…”
Section: (E) Allelic Polymorphisms In Sulfur Metabolism Genes and Amentioning
confidence: 99%